MATERI PEMBELAJARAN EKOLOGI HEWAN: POLA DIVERSITAS KOMUNITAS GASTROPODA EKOSISTEM MANGROVE CILACAP - KARYANTO, PUGUH; HADISUSANTO, SUWARNO (Bioedukasi: Jurnal Pendidikan Biologi, 2005)
Cilacap Mangrove Forest is the largest mangrove ecosystem in Java. Some differences in term of environmental condition are founded among that ecosystem, as a result of sedimentation, deforestation, industrial activity and conservation. Those differences could lead the difference of associated gastropod community in term of their diversity. The aim of this research was to know the diversity pattern of mangrove gastropod community of Cilacap mangrove ecosystem.Study site was divided into 5 station based on the dominant vegetation, mangrove conservation, the presence of polluting activity and acretion phenomena. Transects and plots were used to take the best representation of sampling by giving 5 transects and 5 alternating plot (size 4X4 m) for each transect in every station. Transects were placed perpendicular to the river/coast line. Diversity indexes were then calculatedaccording to Shannon-Wiener formula.The result showed that the highest diversity was founded in the non-accretic station, followed by conservation station, accretic station, polluted station and the least was Nypa-dominated station. Soil and water salinity, pollution, mangrove stage and its species richness were the main environmental factor driving the absence or presence of the gastropod species, thus influenced the community diversity.